Students' Proportional Reasoning in Solving PISA Problems on Quantity Content: An Analysis from the Perspective of Mathematical Self-Efficacy - Windasari, Fany Dania; Setyaningsih, Nining (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
One of the abilities that students need to develop is proportional thinking. Mathematical problems and real-world situations involving the connection between numbers and comparisons need students to use their reasoning skills to reach conclusions. The purpose of this study is to characterize, in terms of self-efficacy, students' proportional reasoning skills when addressing quantity content PISA questions. The self-efficacy questionnaire, PISA questions on quantitative content, interview instructions, and documentation are among the instruments used in this descriptive qualitative study. The study's findings demonstrate that students with low self-efficacy struggle to meet proportional reasoning requirements, contemplate difficulties, and give up quickly out of fear of failing, Pupils rely on guesswork to solve issues instead than attempting to come up with novel solutions. Students with moderate self-efficacy can identify proportional quantities in problems and understand them, but they are not yet able to convert quantities into other forms. They can also use the appropriate strategy but are still hesitant and make mistakes when calculating. Students with moderate self-efficacy are eager to work on problems, but they give up easily when faced with challenging ones. However, despite their continued self-doubt, students continue to look for answers. Despite their restricted talents, students who possess strong self-efficacy are able to meet proportional reasoning markers. Students who have high self efficacy tend to have motivation, high enthusiasm and have confidence in their abilities, students will try to find new ideas to solve problems.